“De røller R” - Line Krogager Andersen; Line Møller Daugaard (Acta Didactica Norden, 2023)
In this article, we illustrate how language awareness emerges and evolves through social interaction when students and teachers collaboratively construct beliefs, analyses and understandings of linguistic phenomena and the concept of language as such. The article is a case study of specific forms of manifestation of language awareness in a particular plurilingual context, focusing primarily on one particular student, and considering the ways in which he engages with language in the situated and evolving context of plurilingual language weeks in year 9. The study is based on an extensive selection of empirical data gathered as part of a larger research project investigating language awareness across educational levels, and revolves around student whose ways of manifesting language awareness in the eyes of the authors constituted a rich empirical point for several reasons: the emergent Danish which shapes his manifestations of language awareness in unexpected ways; the observable social origin of particular loci of metalinguistic attention and the ways in which his manifestations of language awareness are both grounded in, shaped by and ultimately shape his position in group work. We analyse each of these perspectives on our focal student’s manifestations of language awareness in three analytical steps, drawing on empirical classroom data in the form of student worksheets, notes and discussions in group work, as well as interview data. We conclude by discussing how the reflections of this three-step analysis affect our theoretical and empirical notion of language awareness as enacted and emergent in the classroom context.